Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Digital Startup - Dicky Aditia; Fitra Dharma; Retno Yuni Nur (Penerbit Goodwood, 2022)
Purpose: Based on the liquidity ratios, profitability ratios, solvency ratios, and activity ratios of digital startup businesses listed on the Indonesia Stock Exchange in 2017–2021, this study seeks to ascertain the impact of financial performance the value of a firm. Research methodology: Purposive sampling was utilized in this study to narrow down the sample until a final sample of 12 firms was chosen. It became clear that the study data were typically dispersed during the observation time. No variables departed from the conventional assumptions according to the test of normality, test of multicollinearity, test of heteroscedasticity, and test of autocorrelation. This demonstrates that the multiple-linear regression equation model's criteria were satisfied by the data that was provided. Results: The study's findings demonstrate that while the activity ratio has a considerable positive impact on business value, the liquidity ratio, profitability ratio, and solvency ratio do not. Limitations: The year of observation is still fairly short and there are only four independent variables. Contribution: This study is anticipated to be helpful for investors in making decisions, researchers in expanding their knowledge, and businesses in formulating regulations.